ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT INDIGENOUS DARI FERMENTASI ALAMI BIJI KAKAO SEBAGAI KANDIDAT AGEN ANTIKAPANG - Nurul Isnaini Fitriyana; Sony Suwasono; Joni Kusnadi (Agroindustrial Technology, University of Trunojoyo Madura, 2015)
This research have focused on isolation and identification of lactic acidbacteria (LAB) with potential antifungal which candidate as biopreservativemicroorganisms. LAB produce bioactive compound with antifungal activity. Thus, of atotal of 69 lactic acid bacteria isolated and 39 isolates further tested its antifungalactivity. Indigenous moulds that will be tested for antifungal activity of LAB wereobtained from unfermented cocoa beans. There were black mould (allegedly Aspergillusniger), green mould (allegedly Aspergillus fumigatus) and grayish white mold (allegedly Mucorspp.). Thus, 18 isolates of LAB that could inhibit all of three types of fungi further identified in aphenotype, 3 isolates of LAB with highest antifungal activity in identification with API 50 CHLmethod and identified as Lactobacillus fermentum, with a different value of ID value, ID99,8% (F1L-6an) criteria : very good identification; ID 99.9% (F1L-6dsr), criteria : verygood identification , and ID 89.8% (F3L-7P) criteria : very good identification to the genus .LAB isolates obtained can be used as starter cultures to improve the quality offermentation to inhibit the growth of mould, mycotoxin production, and fungicideresidues so as to improve quality, safety of cocoa concumption, and increase the priceof Indonesian cocoa bean exports.